2018
DOI: 10.1111/nph.15529
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐scale genome assembly reveals a highly dynamic effector repertoire of wheat powdery mildew

Abstract: Summary Blumeria graminis f. sp. tritici ( B.g. tritici ) is the causal agent of the wheat powdery mildew disease. The highly fragmented B.g. tritici genome available so far has prevented a systematic analysis of effector genes that are known to be involved in host adaptation. To study the diversity and evolution of effector genes we produced a chromosome‐scale assembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(160 citation statements)
references
References 48 publications
(107 reference statements)
10
150
0
Order By: Relevance
“…Examples comprise the wheat pathogens Zymoseptoria tritici[67] and Blumeria graminis f. sp. tritici[68], and the broad host range pathogen Verticillium dahlia[69]. Moreover, different strains can encode different alleles of the same effector gene; this was, for example, reported for the low complexity regions containing Ustilago maydis effector Rsp3[58].Several reports suggest that effector proteins containing low complexity regions can play important roles in virulence[37,70], and results presented in the present work suggest that different fungal lifestyles contribute to the evolution of low complexity regions in effector proteins.ConclusionsA comparative genomics study with 121 plant colonizing fungi representing six different lifestyles showed that protein type (cytoplasmic or secreted), protein age (ancestral proteins conserved in most species or recent species-specific proteins), and lifestyle of different fungal species contribute to the evolution of low complexity regions in effector proteins.…”
supporting
confidence: 76%
“…Examples comprise the wheat pathogens Zymoseptoria tritici[67] and Blumeria graminis f. sp. tritici[68], and the broad host range pathogen Verticillium dahlia[69]. Moreover, different strains can encode different alleles of the same effector gene; this was, for example, reported for the low complexity regions containing Ustilago maydis effector Rsp3[58].Several reports suggest that effector proteins containing low complexity regions can play important roles in virulence[37,70], and results presented in the present work suggest that different fungal lifestyles contribute to the evolution of low complexity regions in effector proteins.ConclusionsA comparative genomics study with 121 plant colonizing fungi representing six different lifestyles showed that protein type (cytoplasmic or secreted), protein age (ancestral proteins conserved in most species or recent species-specific proteins), and lifestyle of different fungal species contribute to the evolution of low complexity regions in effector proteins.…”
supporting
confidence: 76%
“…In addition, all chromosomes contain a putative centromere region of variable length (Figure 3), which is, as in other fungi, characterized by high transposable element density, low gene density, absence of gene transcription and reduced CG-content (Müller et al , 2019; Smith et al , 2012; Yadav et al , 2018). Putative centromere regions were located within chromosomal regions avoid of recombination, consistent with the findings from other fungi (Laurent et al , 2018; Mancera et al , 2008; Müller et al , 2019). The exact location and length of centromere regions, however, needs to be confirmed using chromatin immunoprecipitation sequencing (CHIPseq) as applied in other basidiomycetes (Yadav et al , 2018).…”
Section: Discussionmentioning
confidence: 90%
“…The most striking deviations in these patterns are recombination hotspots. Such recombination hotspots are observed in many fungal species (Croll et al , 2015; Laurent et al , 2018; Müller et al , 2019; Roth et al , 2018; Van Kan et al , 2017), however their specific role in genome and gene evolution is still largely unknown. In the wheat pathogen Zymoseptoria tritic recombination hotspots may serve as ephemeral genome compartments favoring the emergence of fast-evolving virulence genes (Croll et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the powdery mildew pathogen Blumeria graminis, putative effectors and some known Avr genes occur in physically co-located gene clusters that have resulted from tandem duplications. The presence/absence of specific paralogous effectors is very variable between different B. graminis strains (Müller et al, 2019).…”
Section: Application Of the D N /D S Ratio Test To Plant Pathogens: Lmentioning
confidence: 99%